Combining gold and palladium catalysis: one-pot access to pentasubstituted arenes from Furan-Yne and En-Diyne substrates - Hashmi, A. Stephen K.; Ghanbari, Mohammad; Rudolph, Matthias; Rominger, Frank (Chemistry - a European journal, 2012)
A series of furan-yne systems was transformed into the corresponding tetrasubstituted annelated phenol derivatives that bear one bromo group. The two-step procedure consisted of a phenol synthesis and a subsequent electrophilic bromination with N-bromosuccinimide (NBS). The reactions can be performed in a one-pot procedure with the same precatalyst. The halogenation reaction is highly selective only in the presence of the gold catalyst. En-diyne substrates were also suitable starting materials; then the pentasubstituted aromatic core showed a completely different substitution pattern for the phenolic products. Furthermore, a one-pot protocol that consisted of a gold-catalyzed phenol synthesis, a gold-catalyzed halogenation reaction, and a palladium-catalyzed Suzuki coupling was established. The overall efficiency of this procedure was excellent and the substrate scope of the reaction was broad.